Back to Where It Was First Described: Vectors of Sylvatic Yellow Fever Transmission in the 2017 Outbreak in Espírito Santo, Brazil - Luciana Matos de Abreu Stanzani; Monique de Albuquerque Motta; Rafael Santos Erbisti; Filipe Vieira Santos de Abreu; Agostinho Cardoso Nascimento-Pereira; Anielly Ferreira-de-Brito; Maycon Sebastião Alberto Santos Neves; Gláucio Rocha Pereira; Glauber Rocha Pereira; Claudiney Biral dos Santos; Israel de Souza Pinto; Creuza Rachel Vicente; et al. (Viruses, 2022)
Evidence of sylvatic yellow fever was first reported in Atlantic Forest areas in Espírito Santo, Brazil, during a yellow fever virus (YFV) outbreak in 1931. An entomological survey was conducted in six forest sites during and after an outbreak reported ~80 years after the last case in the area. Among 10,658 mosquitoes of 78 species, Haemagogus leucocelaenus, and Hg. janthinomys/capricornii were considered the main vectors as they had a relatively high abundance, co-occurred in essentially all areas, and showed high YFV infection rates. Sabethes chloropterus, Sa. soperi, Sa. identicus, Aedes aureolineatus, and Shannoniana fluviatilis may have a secondary role in transmission. This is the first report of Sa. identicus, Ae. aureolineatus, and Sh. fluviatilis infected with YFV. Our study emphasizes the importance of entomological monitoring and maintenance of high vaccination coverage in receptive areas to YFV transmission.